Researcher training for the field of Education Policy: literature review - Andréa de Paula Pires (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2019)
This paper presents a literature review focused on the education of researchers for the education policy field. Six studies related to this topic were found (TELLO, 2015; 2017; GOROSTIAGA, 2017; DALPIAZ, 2017; MAINARDES; STREMEL, 2017; 2019). The results of the review showed that the process of education for research in Education Policy is still scarce, since this is a recent field of research that has not been fully explored. However, the texts found discuss important elements of this theme. It seems relevant to emphasize that this is an important theme, since the development of researchers is associated to the future of this field and its consolidation. The works included in the review were observed to present certain convergence regarding their discourse about the theme, mainly, when addressing the importance of the teaching/learning process in the development of the researcher for the Education Policy field, as well as in relation to theoretical-epistemological issues, mainly the epistemologies of the Education Policy.